The Effect of Using Lingodeer Application on Students’ Vocabulary of the Seventh Grade at MTS Darul Ilmi Batang Kuis - Prawita Sitepu, Fadila Menda; Putri, Rini Fadhillah (Universitas Negeri Medan, 2024)
There are several factors that affect vocabulary teaching. A creative teacher will use teaching methods that are appropriate to the conditions of the students in the class and can attract them to be more interested in learning English, especially vocabulary mastery. The purpose of this study was to find the significance of Lingodeer Application in teaching English Vocabulary which was observed and analyzed by the seventh grade students of MTS Darul Ilmi Batang Kuis. In this research method is quantitative by taking 60 students as a sample. The population of this study were all students of class VII and the sample of this study was class VII- 1 as the experimental class, class VII- 2 as the control class. The research instrument used was multiple choice. Research on the use of Lingodeer Application and the Lingodeer Application has a significant effect on students' vocabulary achievement. It can be concluded that the use of Lingodeer Application in improving students' vocabulary mastery is affective. The results found in this study were observed t of 8,85 and 1 table of 2.00. This can be stated that there is a significant difference between the vocabulary scores of students who are taught using Lingodeer Application and without Lingodeer Application. It means that Lingodeer Application is quite effective in increasing students' vocabulary achievement.